Analisis Kualitatif Pengisian Rekam Medis Rawat Inap Di Rumah Sakit Umum Daerah Kabupaten Aceh Tamiang Tahun 2022 - Zulham Andi Ritonga; Ali Sabela Hasibuan; Tasya Adinda Putri (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Completeness of filling out medical records in hospitals is a must for health workers and can be done using qualitative analysis. The purpose of this study was to determine the qualitative analysis of filling in inpatient medical records at the Aceh Tamiang District General Hospital. This research is a descriptive research with a quantitative approach. The research was conducted at the Aceh Tamiang District Hospital. The population in this study was 1,840 and the sample obtained was 95 inpatient medical records. The results showed that the review of the completeness and consistency of the diagnosis was 90 (95%) accurate and 5 (5%) inaccurate, namely in the inpatient doctor's notes. In the notes and nursing care and nursing diagnoses there were 87 (92%) complete and 8 (8%) incomplete. Review of the consistency of recording the diagnosis, there were 85 (89%) complete and 10 (11%) incomplete. There are 83 medical records (87%) accurate and 12 (13%) inaccurate. Incomplete and inaccurate filling of inpatient medical records is found in the consistency of development records and nursing care. There were 82 (86%) complete and 13 (14%) incomplete records of things that were carried out during treatment and treatment, namely on evidence of implementation of treatment plans, instructions and drug changes, and actions taken which were filled out by nurses. Review of informed consent from 16 inpatient medical records, there were 14 (87%) complete and 2 (13%) incomplete, namely the completeness of the contents of the informed consent filled out by nurses. Review of medical methods or practices, there are 84 (88%) complete and 11 (12%) incomplete, namely on the date and time, the signature / initials is easy to read filled in by the doctor